Perioperative Pregabalin for Preventive Analgesia in Breast Cancer Surgery: A Meta-analysis of Randomized Controlled Trials. Issue 12 (December 2020) - Chang, Chun-Chia; Yen, Wei-Ting; Lin, Yao-Tsung; Wang, Li-Kai; Hung, Kuo-Chuan; Wu, Zhi-Fu; Chen, Jen-Yin
Abstract : Objectives: Pregabalin is a drug for neuropathic pain. Antipronociceptive properties of pregabalin have led to its recent use as an adjuvant to the multimodal postoperative pain regimen. This meta-analysis was conducted to evaluate the efficacy of perioperative pregabalin on acute and chronic postsurgical pain (CPSP) after breast cancer surgery. Methods: A meta-analysis including 8 randomized controlled trials searched from MEDLINE, EMBASE, and the Cochrane Central Register of Controlled Trials was conducted. Subgroup analysis was performed according to doses and timecourse of pregabalin administration. Review Manager 5.3 was selected to conduct the meta-analysis. Results: Preoperative pregabalin in breast cancer surgery alleviated acute postoperative pain at rest 24 hours after surgery by 0.31 points on an 0 to 10 Numerical Rating Scale (95% confidence interval [CI] −0.57 to −0.05). Morphine consumption showed a decrease in postoperative use by 1.09 mg (95% CI: −1.61 to −0.57). The incidence of CPSP 3 months after surgery was reduced to 46% (95% CI: 0.25-0.85). Postoperative nausea and vomiting, dizziness, and sedation showed no overall significant reductions. However, a decrease in the incidence of postoperative nausea and vomiting and an increase in the incidence of dizziness were noted when patients received 300 mg of pregabalin before surgery. Discussion: This study demonstrated that pregabalin showed more efficacy on chronic pain than acute pain after a breast cancer surgery. Further study based on doses and treatment course of pregabalin should be conducted to establish stronger evidence of treatment effects. Abstract : Supplemental Digital Content is available in the text.